Model-Based Control for Dual-Fuel Engines - Ichihashi, Hiroaki; Yamasaki, Yudai; Takashima, Yoshitane; Sako, Takahiro (Frontiers in Mechanical Engineering, 2020)
For the effective use of natural gas, a dual-fuel engine (DFE) has been paid attention to. It was known that in DFE, the combustion efficiency of the natural gas decrease at a low load. Against this problem, it has been reported that the combustion efficiency can be improved by multi-stage diesel injection. Therefore, in this research, the mechanism was clarified why the combustion efficiency improves by multi-injection diesel injection, and a control model was constructed that predicts the combustion efficiency assuming multi-stage injection. Furthermore, using the control model, a controller was designed to maximize the combustion efficiency by adjusting the diesel injection conditions. As a result, the combustion efficiency improved by using this controller. Furthermore, by considering the heat ratio of natural gas against diesel fuel in addition to the combustion efficiency, a possibility was shown to design a controller to leverage the advantage of DFE, which reduces the amount of fossil fuel.